Single-Strand Consensus Sequencing Reveals that HIV Type but not Subtype Significantly Impacts Viral Mutation Frequencies and Spectra. Issue 15 (21st July 2017) - Rawson, Jonathan M.O.; Gohl, Daryl M.; Landman, Sean R.; Roth, Megan E.; Meissner, Morgan E.; Peterson, Tara S.; Hodges, James S.; Beckman, Kenneth B.; Mansky, Louis M.
Abstract: A long-standing question of human immunodeficiency virus (HIV) genetic variation and evolution has been whether differences exist in mutation rate and/or mutation spectra among HIV types (i.e., HIV-1 versus HIV-2) and among HIV groups (i.e., HIV-1 groups M–P and HIV-2 groups A–H) and HIV-1 Group M subtypes (i.e., subtypes A–D, F–H, and J–K). To address this, we developed a new single-strand consensus sequencing assay for the determination of HIV mutation frequencies and spectra using the Illumina sequencing platform. This assay enables parallel and standardized comparison of HIV mutagenesis among various viral vectors with lower background error than traditional methods of Illumina library preparation. We found significant differences in viral mutagenesis between HIV types but intriguingly no significant differences among HIV-1 Group M subtypes. More specifically, HIV-1 exhibited higher transition frequencies than HIV-2, due mostly to single G-to-A mutations and (to a lesser extent) G-to-A hypermutation. These data suggest that HIV-2 RT exhibits higher fidelity during viral replication, and taken together, these findings demonstrate that HIV type but not subtype significantly affects viral mutation frequencies and spectra. These differences may inform antiviral and vaccine strategies. Graphical Abstract: Highlights: Goal: Determine if differences exist in mutation rates and/or spectra among HIV types or subtypes. A new single-strand consensus sequencing assay was developed. Significant differences found in viral mutagenesis between HIV types but not among subtypes. HIV type but not subtype significantly impacts viral mutation frequencies and spectra.